Vectors of Transformation of Civil Activity of Russian Youth in the First Third of the 21st Century - Kirill Makarenko (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
Introduction. The adaptation mechanism of the state as a political institution determines the vectors of transformation of social interactions in the event of significant external and internal crises. Overcoming the consequences of the COVID-19 pandemic and the conduct of a special military operation by Russia in Ukraine leads to the formation of a new system of relations between the government and society, when the growth of trust in political institutions leads to the “shift” of local problems to the federal national level. Methods and materials. The methodological basis of the study is the theory of collective identity and individual provisions of the theory of rational choice. The empirical basis of the study is public opinion polls on the practices and forms of civic engagement, conducted by the largest domestic sociological centers. Specific research methods are statistical analysis of posts in Telegram, visualization by constructing a boxplot, and a histogram of the distribution of reactions to posts. An analysis of the forms and practices of civic engagement of young people in the Russian Federation during the COVID-19 and military operation periods showed that as a result of the increase in the level of political, institutional, and generalized trust in Russia, a number of vectors have been formed, the direction of which is dictated by the special military operation. Results. If the trend towards online, inclusivity, and locality is characteristic of civic engagement in countries that are not going through the crisis stage, then in Russia 2022–2024 the focus is determined by the mechanism of “civic mobilization,” which is characterized by 1) digitalization; 2) a temporary shift in the scale of actions from the local to the federal level; and 3) a general increase in civic engagement among young people. Funding. The work was carried out with the financial support of the Ministry of Education and Science of the Russian Federation and the Expert Institute for Social Research within the framework of the FZUU-2024-0005 project “Participation in elections as a family tradition: resources of the family institute and vectors of mobilization of civic engagement of modern Russian youth.”